Dynamic interactions between a membrane binding protein and lipids induce fluctuating diffusivity - Yamamoto, E; Akimoto, T; Kalli, A; Yasuoka, K; Sansom, M (American Association for the Advancement of Science, 2017)
Pleckstrin homology (PH) domains are membrane-binding lipid recognition proteins which interact with phosphatidyl-inositol-phosphate (PIP) molecules in eukaryotic cell membranes. Diffusion of PH domains plays a critical role in biological reactions on the membrane surfaces. Although diffusivity can be estimated by long-time measurements, it lacks information on the shorttime diffusive nature. Here, we reveal two diffusive properties of a PH domain bound to the surface of a PIP-containing membrane using molecular dynamics simulations. One is fractional Brownian motion, attributed to the motion of the lipids with which the PH domain interacts. The other is temporally fluctuating diffusivity, i.e. the short-time diffusivity of the bound protein changes substantially with time. Moreover, the diffusivity for short-time measurements is intrinsically different from that for long-time measurements. This fluctuating diffusivity results from dynamic changes in interactions between the PH domain and PIP molecules. Our results provide evidence that the complexity of protein-lipid interactions plays a crucial role in the diffusion of proteins on biological membrane surfaces. Changes in the diffusivity of PH domains and related membrane-bound proteins may in turn contribute to the formation/dissolution of protein complexes in membranes.